DESIGN AND ANALYSIS OF DOUBLE-PIPE HEAT EXCHANGER USING BOTH HELICAL AND ROTATING INNER PIPE - Koca, Tarkan; Citlak, Aydin (Vinca Inst Nuclear Sci, 2021)
In this study, the effects of rotating straight and helical inner tubes is experimentally discussed to determine heat transfer and pressure losses in rotating tubes and improve heat transfer. The outer tube remains stationary and the inner tube is rotated at different speeds in the work. In the experiments for straight and helical tubes, the flow regime is turbulent. According to the results, Nusselt number, pressure loss, and efficiency of heat exchanger were gauged. In addition, empirical formulas were obtained for each pipe type. It is observed that as the rotation speed of the pipe increases, the heat transfer rate increases. The pipe that provides the best increase in heat transfer is the five helixes tubes. At five helixes tubes; after the number of revolutions per minute exceeds 300, the increase in heat transfer rate has almost halt. At five helixes tubes and at 300 rpm speed when the flow of cold water through the annular gap with the fluid passing through the inner tube is equal, the heat transfer increases by 124.10% compared to straight tube, 23.47% compared to two helixes tubes, 7.92% compared to three helixes tubes, and 1.65% compared to four helixes tubes. Maximum effectiveness was obtained while rotating with 300 rpm in five helixes pipes.
Keywords: double-pipe heat exchanger; helical tubes; rotationally inner pipe; effectiveness; experimental; thermal science